NOTES ON THE PROFILE OF INDONESIAN INVASIVE ALIEN PLANT SPECIES - Sri Sudarmiyati Tjitrosoedirjo (BIOTROPIA, 2007)
An alien species, which becomes established in natural or semi-natural ecosystems or habitas, is an agent of change and threatens native biological diversity.  The Convention on Biological Diversity (CBD) declared in 1992, in which the issue on invasive alien species was raised, was ratified by the Indonesian Government in 1994.  Protecting our biodiversity will be our moral obligation to comply with CBD.  Inventory on the invasive alien plant species in Indonesia should be done by field surveys aside from the data collected from the references and herbarium specimens.  Field studies should be carried out to get complete figures, to identify the new ones, to determine their distributions, to plan their management including prevention to spread, containment and movement or mitigate their impact to environment.  Sometimes it is difficult in determining whether the plants are aliens or not. Cooperation with botanists and taxonomists in other parts of the world is necessary.  There are some species of invasive aliens plant in Indonesia, which have to be watched for their aggressiveness i.e. Acasia nilotica (L.) Willd. ex Del., Eupatorium sordidum Less., Jatropa gossipifolia L., Mikania micrantha Kunth, Mimosa pigra L., Opuntia sp., and Piper aduncum L. have to be watch for their aggressiveness.  Notes on some important invasive alien plant species are discussed.